A family history of illness : memory as medicine - Walker, Brett L., 1967- (University of Washington Press, 2018)
"In this deeply personal narrative, Brett L. Walker sets out to construct a history of his body and family health in an effort of better understanding his diagnosis with a serious immunological disorder in 2010. While succumbing to pneumonia and a plural effusion in an Intensive Care Unit, a doctor's simple question, 'Do you have a family history of illness?' launched Walker's investigation into his and his family's medical past. The final product represents a startlingly fresh way to view the role of history in understanding our physical selves and, in the broader sense, the communities where we live. In his family's history, Walker discovers something far more valuable than a predisposition to an immunological disorder. He concludes that family stories are what shape us and color our world. Walker's relationship with rural life on a Montana wheat and barley farm are what he continues to rehearse in his own imagination. He discovers that family is at the root of identity and values. Without ties to a family history, we are like wheat waving in the wind. This, he concludes, is the more lasting lesson of history. Walker submits that, at a time when only the present seems to matter, we must renew our interest in the past, or risk misunderstanding our selves and the world around us"--Provided by publisher.